2022
DOI: 10.5114/jcb.2022.114929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of applicator removal from target volume for cervical cancer patients treated with Venezia high-dose-rate brachytherapy applicator

Abstract: Purpose The volume of Venezia applicator with vaginal caps can be relatively large compared to target volumes. This study investigated the dosimetric and radiobiological effects of applicator volume removal for cervical cancer patients treated with Venezia (VZ) and tandem and split-ring (TSR) applicators used in the clinic. Material and methods A total of 40 patients (101 plans) with stage IIA-IIIC cervical cancer were retrospectively reviewed. Thirty patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In the present study, 83% of patients with AJCC stage II tumors achieved LC at 5 years, which was fewer than stage I patients, and patients in the RetroEMBRACE study, which reported LC at 5 years in 94% of stage IIA patients and 91% in stage IIB patients. These suggest that the higher HR-CTV doses in the RetroEMBRACE benefited AJCC stage II patients (mean HR-CTV D 90 of 71.9 Gy vs. ≥ 88 Gy in the RetroEMBRACE study) [ 17 , 18 ]. Thus, the lower LC in AJCC stage II patients in our study could be due to the difficulty of covering the target volume with only endocavitary brachytherapy techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 83% of patients with AJCC stage II tumors achieved LC at 5 years, which was fewer than stage I patients, and patients in the RetroEMBRACE study, which reported LC at 5 years in 94% of stage IIA patients and 91% in stage IIB patients. These suggest that the higher HR-CTV doses in the RetroEMBRACE benefited AJCC stage II patients (mean HR-CTV D 90 of 71.9 Gy vs. ≥ 88 Gy in the RetroEMBRACE study) [ 17 , 18 ]. Thus, the lower LC in AJCC stage II patients in our study could be due to the difficulty of covering the target volume with only endocavitary brachytherapy techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Such an applicator causes deformation of the surrounding tissues, hindering the correct segmentation [ 33 ]. Additionally, the high dose gradient in the vicinity of the applicator may impact the accuracy of the surrounding tissues’ DVH dosimetric parameters [ 34 , 35 ]. These issues will increase the dose uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…This was a review of 27 consecutive patients receiving IC or IC/IS brachytherapy boost during definitive treatment for cervical cancer at a single academic medical center between 2019 and 2021. The randomized patient cohort was based on brachytherapy treatments administered using either the Geneva or Venezia tandem and ovoid IC/IS brachytherapy applicator [19][20][21] (Elekta, Inc.). For each brachytherapy treatment, an IC or IC/IS tandem and ovoid applicator was placed under anesthesia by an experienced physician using standard methods [8,22].…”
Section: Patient Cohortmentioning
confidence: 99%